Augmented Reality Based Competency Based Learning on Computer Network Learning in Vocational Education Vocational School - Efendi, Raimon; Ali, Gunawan; Andang Purnomo, Wulan; Iskandar, Iskandar; Agustin Wulandari, Ratih (LPPM Undiksha, 2023)
This research is motivated by the complexity of the subject matter of Computer Networks, the large number of teachers who teach these subjects with different backgrounds, and not all of them can be practised directly due to limited laboratory facilities, accompanied by a learning model that is not yet competency-based which also makes learning outcomes not optimal. This study aims to develop three-dimensional computer network learning media using Augmented Reality Assembly Edu software in vocational education. This type of research is created using the ADDIE model, which includes analysis, design, development, implementation, and evaluation. Collection methods using observation and interviews. The data collection instrument used a questionnaire. Data analysis techniques using qualitative and quantitative descriptive analysis. The results showed that Competency-based learning-based Augmented Reality media, validated by a team of media experts and material experts, was very valid. In contrast, students stated well because this media made it easier to understand the material and motivated them to try and learn. It was concluded that Competency-based learning-based Augmented Reality media could be used in learning.